COMPARISON OF MODULY OF ELASTICITY OBTAINED BY NON-DESTRUCTIVE AND DESTRUCTIVE TESTS OF TIMBER SAMPLES (Advances in Civil and Architectural Engineering, 2021)
In this paper, we used non-destructive techniques (NDTs) and destructive techniques (DTs) to assess the mechanical properties of structure-sized timber members. The experiments included several NDTs—hygrometric, ultrasonic, and resistographic methods—as well as static bending and compression tests parallel to the grain. Using a linear regression model, we correlated the NDT and DT parameters.